2017
DOI: 10.1001/jamaneurol.2017.0143
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Predictors of 5-Year Outcome After Concussive Blast Traumatic Brain Injury

Abstract: The long-term clinical effects of wartime traumatic brain injuries (TBIs), most of which are mild, remain incompletely described. Current medical disability cost estimates from world conflicts continually surpass projections. Additional information regarding long-term functional trajectory is needed to reduce this extensive public health burden.OBJECTIVES To examine 5-year clinical outcomes leveraging existing clinical data collected at 1 year after injury in the same patients and to identify early risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 67 publications
2
86
0
1
Order By: Relevance
“…107 Furthermore, a decline in outcomes from 1 year to 5 years after injury was recently reported in 36 of 50 (72%) US military service members with concussive blast TBI. 108 Other evidence suggests that TBI is an independent risk factor for stroke. 13 A retrospective case-control study from Taiwan showed that a past history of TBI doubled the risk of stroke (hazard ratio 1•98; 95% CI 1 •86-2•11) and increased post-stroke mortality (odds ratio 1•57; 95% CI 1•13-2•19).…”
Section: The Lancet Neurology Commissionmentioning
confidence: 99%
“…107 Furthermore, a decline in outcomes from 1 year to 5 years after injury was recently reported in 36 of 50 (72%) US military service members with concussive blast TBI. 108 Other evidence suggests that TBI is an independent risk factor for stroke. 13 A retrospective case-control study from Taiwan showed that a past history of TBI doubled the risk of stroke (hazard ratio 1•98; 95% CI 1 •86-2•11) and increased post-stroke mortality (odds ratio 1•57; 95% CI 1•13-2•19).…”
Section: The Lancet Neurology Commissionmentioning
confidence: 99%
“…11 Of importance, much of the empirical literature supporting this conceptualization comes from survivors of moderate or severe TBI, which has been associated with higher rates of disease across multiple body systems 11 and reduced life expectancy compared with the general population. 12 The study by Mac Donald et al 9 provides evidence of deterioration or disease progression but in relatively young individuals exposed to a clinically defined mTBI.…”
mentioning
confidence: 99%
“…In addition to static symptoms that persist, new symptoms may also appear months to years following TBI, including those associated with delayed neurodegeneration and dementia [1,11]. Estimates as to the size of this population vary, but one study of U.S. military service personnel who experienced an mTBI in Iraq or Afghanistan found that-while many improved-about 20% reported the appearance of new symptomatology, such as posttraumatic-stress disorder (PTSD) within 5 years after injury [12,13]. Another study of 188,764 older veterans (mean age of 68 years) revealed that a history of any TBI was associated with a 60% increase in the risk of developing dementia over a 9-year follow up [14][15][16].…”
Section: Introductionmentioning
confidence: 99%